«Αέναο υπόγειο ρεύμα»: Ψυχανάλυση και Αγωγή - Γαλανάκη, Ε. (Η χάρη θέλει αντίχαρη: Αφιέρωμα στον Καθηγητή Αντώνιο Κ. Δανασσή-Αφεντάκη, 2011)
In this essay, we study the relationship between psychoanalysis and education, a relationship that is as old as the history of psychoanalysis itself. Freud’s views on this issue, which appear scattered in his various writings, are identified and synthesized. More specifically, we discuss Freud’s views on the importance of applying psychoanalysis in education, the significance of the educator’s personality, his/her difficulties in understanding children, the “prophylactic” (preventive) role of education, the necessity to adopt an optimum stance between the two poles of permissiveness and frustration, the links of education with sublimation and culture, the limits of education as compared to the individual’s development, etc. These views are discussed in relation to Anna Freud’s systematic elaboration on the relationship between psychoanalysis and education, as well as to various views of contemporary psychoanalysts on the same issue.